HUBUNGAN TEKANAN CUFF DENGAN TINGKAT NYERI TENGGOROKAN PASCA GENERAL ANESTESI INTUBASI ENDOTRACHEAL TUBE (ETT) - Syahrul, Nurul Qalbi; Riyadi, Raden Sugeng; Rohmah, Astika Nur (Jurnal Ilmiah Kesehatan Media Husada, 2025)
Background: The Endotracheal Tube intubation process, used for general anesthesia, involves inserting a tube into the trachea through through the mouth or nose. This can lead to post-procedure discomfort, such as hoarseness or a sore throat. These side effects are often caused by the tube’s pressure on the trachea and the inflation of its cuff. Aim of the Study: The study aimed to determine the relationship between Cuff pressure and the level of throat pain after general anesthesia Endotracheal Tube (ETT) intubation at PKU Muhammadiyah Hospital, Bantul. Research Method: This study employed a quantitative research design using correlation analysis to investigate the relationship between cuff pressure during endotracheal intubation and post-operative sore throat. Non-probability sampling was utilized to select 57 participants. Cuff pressure was measured using a specialized tool, and pos-toperative sore throat severity was assessed through observation. Spearman rank correlation analysis was conducted to analyze the data. Findings: This research found that most of the cuff pressure was in 20cmH2O - 30cmH2O or normal cuff pressure for 20 respondents (64.9%). Most respondents (50.9%), or 29 of them, experienced sore throat in this study. The results of the relationship test between Endotracheal Tube (ETT) Cuff pressure and sore throat after general anesthesia using the Spearman rank test obtained a significant p-value of 0.000 (<0.05) and a correlation coefficient value of 0.568. Conclusion: There is a relationship between ETT Cuff pressure and cases of sore throat after general anesthesia at PKU Muhammadiyah Hospital, Bantul. Suggestion: Further researchers are expected to be able to relate between ETT Cuff pressure and the level of throat pain with different variables.